SUSTAINABILITY OF TOURISM AND THE ENVIRONMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The tourism sector faces many important sustainability challenges. Specific challenges to be addressed include CO2 emissions, water consumption, landscape degradation and biodiversity loss. Environmentally sustainable tourism can be considered as a level of tourism that can be realised on the basis of a sustainable or stable environment. The aim of the work is to illustrate the compromises linked to the quest for sustainability in tourism in terms of the environment. The study uses a monographic method for mapping the theoretical frame, quantitative research methods. Bibliometric analysis of academic studies on sustainable tourism and the environment have been carried out. The author conclude that tourism is sustainable, taking full account of its current and future economic, social and environmental impacts in meeting the needs of visitors, industry, environment and business communities.